Hambatan Pembelajaran IPS pada Sekolah Satu Atap - Mira Embun Dini; Maria Montessori; Desi Nora (Dinasti Research, 2022)
The background of this research is the emergence of several obstacles in the implementation of social studies learning at SMP Negeri 23 Batam which is a one-roof school. So far, learning problems have always been assessed in terms of the background of students who are island children where they are identified with children who are lazy and have a low learning ethic. Researchers believe that the problem is not only from the side of the students but also from the side of the teaching staff and all elements that support the learning process. The purpose of this study was to explain the barriers to social studies learning in one-roof schools from the point of view of the teaching staff and all parties involved. The research location was carried out at SMP Negeri 23 Batam which is a one-roof school. The research method used is descriptive qualitative. Instruments and data collection techniques are observation, interviews. Data analysis techniques are data reduction, data presentation, drawing conclusions. The conclusion of this research is that there are several problems that become obstacles to Social Studies learning in One-Roof schools, namely the not yet optimal use of eco media or simple media as learning by teachers in schools, the not optimal use of smartphones to introduce digital media for learning in schools, the need to improve the ethos the work of teaching staff in island schools, the teaching and non-educational staff in schools are not optimal yet towards excellent service, the implementation of rules and regulations in schools is not yet optimal